If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11m(21m + 10) = 0 Reorder the terms: 11m(10 + 21m) = 0 (10 * 11m + 21m * 11m) = 0 (110m + 231m2) = 0 Solving 110m + 231m2 = 0 Solving for variable 'm'. Factor out the Greatest Common Factor (GCF), '11m'. 11m(10 + 21m) = 0 Ignore the factor 11.Subproblem 1
Set the factor 'm' equal to zero and attempt to solve: Simplifying m = 0 Solving m = 0 Move all terms containing m to the left, all other terms to the right. Simplifying m = 0Subproblem 2
Set the factor '(10 + 21m)' equal to zero and attempt to solve: Simplifying 10 + 21m = 0 Solving 10 + 21m = 0 Move all terms containing m to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 21m = 0 + -10 Combine like terms: 10 + -10 = 0 0 + 21m = 0 + -10 21m = 0 + -10 Combine like terms: 0 + -10 = -10 21m = -10 Divide each side by '21'. m = -0.4761904762 Simplifying m = -0.4761904762Solution
m = {0, -0.4761904762}
| 4x+2=14x-6 | | (9x-4)(x-1)= | | 10x-1=5x+49 | | 6x-8=7-x | | 4(2m-3)=-44 | | 4x-6=10x+14 | | 19=-4(h+5)+h | | x+3-2x+5=10 | | 2x-2=5x-12 | | 4w^2=4w+3 | | 7x-3x=45-4x | | 35=(2x+3)*x | | 6x+5=4x-4 | | 2*1/3+2/1/3=x | | 4x-2x-2=2x | | -(8x-1)+x=-6x+6(x+6) | | x+2=-2x^2 | | 18x^3y-6x^7y=0 | | 2.3w-3.2+4.1=-6 | | 6x+14=29 | | 9t^2+2=9t | | 6x^2-21x-45=0 | | 7c^2-2c=1 | | 25x^3+5x^2-10x-2=0 | | m^2-14m+49=0 | | x^2+16x+53= | | -14=8-3a | | x^2+20x-18=0 | | -z^2+6=-5z | | m+2m+(m+10)=180 | | 7x^2-x-1=0 | | 4x-x+4=2x-6+14 |